Gains in Disability-Free Life Expectancy From Elimination of Diseases and Injuries in Japan - Hashimoto, Shuji (Japan Epidemiological Association, 2012)
BACKGROUND: Although disability-free life expectancy has been investigated in Japan, gains from elimination of diseases and injuries have not been examined. METHODS: We used data from the 2007 Japanese national health statistics to calculate the number of years with and without activity limitation that could be expected from eliminating 6 selected diseases and injuries. RESULTS: At birth, the number of expected years of life without and with activity limitation was 70.8 and 8.4, respectively, in males and 74.2 and 11.8 in females. More than 1.0 expected years without activity limitation were gained from eliminating malignant neoplasms and cerebrovascular diseases; smaller gains were observed after eliminating other diseases and injuries. Elimination of cerebrovascular diseases, dementia, and fracture decreased expected years with activities of daily living (ADL) limitation, and elimination of shoulder lesions/low back pain decreased expected years with non-ADL limitation. CONCLUSIONS: Elimination of diseases and injuries increased expected years with and without activity limitation among Japanese, which suggests that improved prevention of those diseases and injuries—including cerebrovascular diseases and dementia—would result in longer disability-free life expectancy and fewer years of severe disability.